Influência da mortalidade e da estrutura etária na cobertura previdenciária - Carolina Portugal Goncalves da Motta (2007)
The retirement plan coverage is important for the population because it provides insurance to workers and their families for losses resulting from a worker's death, disability or age. A majority the literature cites factors related to the labor market as the principal causes of coverage variation, but almost none analyzes the influence of demographic factors. The demographic factors vary and their influence probably varies too. So, if two populations have the same specific tax coverage but different mortality or age structure, the retirement plan coverage isnt necessarily be the same. The aim of this study is to prove that mortality and age distribution influences the retirement plan coverage and to demonstrate how these factors contribute to the differences in coverage. To do this, five states were chosen (Amazonas, Alagoas, Rio de Janeiro, Rio Grande do Sul, and Mato Grosso). To determine the influence of mortality in the retirement coverage, the retirement population of 2000, in each selected State, was projected until 2020, utilizing two different mortalities levels and the same coverage taxes. The retirement coverage that was found in each projection was compared to another that was calculated to the same State. The findings show that selected demographic factors mortality and age structure influenced the number of retirees, and, since they differ from state to state, these factors could contribute to the variations in coverage.The results agreed with the expectations and showed that, with a constant retirement tax, the lower the mortality, the greater the coverage could be. For the selected States and between men and women, an aging distribution of the population contributes to greater retirement coverage. Therefore, the greater the differences between the age distributions, the greater the contribution of the distribution could be.